Microvascular obstruction due to thrombosis and fibrin deposition in myocardial infarction - Emre Aslanger; Seyhun Solakoğlu; Öner Doğan; Murat Sezer; Sabahattin Umman (Türk Kardiyoloji Derneği Arşivi, 2016)
Objective: It is widely known that myocardial damage is not immediately terminated after the elimination of epicardial occlusion in cases of myocardial infarction. In situ thrombosis during epicardial occlusion might contribute to poor myocardial perfusion after reperfusion of an occluded epicardial artery. In the current study, we sought to determine the effects of ischemia and reperfusion on microvascular thrombotic occlusion. Methods: Thirty male Wistar rats were included in the study. After the rats had been anesthetized and thoracotomized, the left coronary artery was occluded for 30 minutes in the first group, and it was occluded for 30 minutes and reperfused for an additional 20 minutes in the second group. Ten rats were used as a sham-operated control group. After completion of the study protocol, excised heart preparations were analyzed by immunohistochemistry and electron microscopy. Results: A significant difference was found between the infarction plus reperfusion group and the other 2 groups, with respect to microvascular fibrin and thrombocyte deposition in immunohistochemistry analysis. These results were confirmed by morphological examination with electron microscopy. Conclusion: In situ fibrin formation accompanies microvascular obstruction in acute myocardial infarction. Our results indicate that additional therapeutic approaches are needed in order to achieve better tissue perfusion in contemporary treatment of acute myocardial infarction after successful reopening of the infarct-related artery.